2022
DOI: 10.1007/s00590-022-03244-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification in primary total hip arthroplasty: risk factor analysis

Abstract: Background Aim is to identify if age, sex, type of posterolateral approach (mini vs standard), surgical time and time from surgery to drainage removal were independent risk factors for heterotopic ossifications after total hip arthroplasty. Materials and methods Patients who underwent a THA with posterolateral approach during a 15 years period were included. The exclusion criteria were absence of X-rays follow-up or HO prophylaxis protocol adoption. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…According to prior studies, potential risk factors for HO formation after THA include male gender, increased age, ethnicity, underlying osteoporosis, cemented prosthesis, bilateral THA procedures, ankylosing spondylitis, hip ankyloses and previous history of HO. 2,4,26,30 No existing treatment modalities will halt the progression of HO once it has begun to form. 31 Existence of post-arthroplasty pain and limited functional improvement increases with the degree of HO.…”
Section: Discussionmentioning
confidence: 99%
“…According to prior studies, potential risk factors for HO formation after THA include male gender, increased age, ethnicity, underlying osteoporosis, cemented prosthesis, bilateral THA procedures, ankylosing spondylitis, hip ankyloses and previous history of HO. 2,4,26,30 No existing treatment modalities will halt the progression of HO once it has begun to form. 31 Existence of post-arthroplasty pain and limited functional improvement increases with the degree of HO.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the prevalence and extent of HO can be reduced with perioperative prophylaxis. 16 The two types of prophylaxis are oral nonsteroidal anti-inflammatory drugs (NSAIDs) and local irradiation of the hip. 1,5,6,16 One study recommended that pharmacologic prophylaxis for HO should be started within the first 48 hours and no later than five days postoperatively.…”
Section: Prophylaxismentioning
confidence: 99%
“…Any heterotopic bone formation with the posterolateral approach has been reported from 22% to 32%, at followup times of 6 to 24 months postoperatively. 5,[14][15][16] With the direct anterior approach (DAA), the prevalence has been reported from 24% to 42% at follow-up times of 6 to 24 months postoperatively. 2,15,17 With the different socalled anterior-based muscle sparing approaches, one study reported a prevalence of 36% with a minimum follow-up of 9 months.…”
Section: Surgical Approach and Prevalencementioning
confidence: 99%
See 2 more Smart Citations